2012
DOI: 10.1074/jbc.m111.324855
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of the Two Mitochondrial Ornithine Carriers Can Be Swapped by Single Mutation in Substrate Binding Site

Abstract: Background: Substrate binding and transport mechanisms of mitochondrial carriers are inadequately understood. Results: The effect of mutations on substrate specificity and transport activity was assessed in two human ornithine carrier isoforms. Conclusion:The substrate specificity and transport rate of the two isoforms are defined by a few residues and can be swapped. Significance: The results show how small substrates can trigger transport in carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 54 publications
1
52
0
Order By: Relevance
“…The yeast ADP/ATP carriers have one brace and three salt bridges in the extended matrix network, providing a significant energy barrier that prevents conversion to the m-state in the absence of substrate. A single substrate-binding site has been identified in the central cavity, which corresponds to the middle of the membrane (25,29). There is consensus on the residues involved in ADP binding to the ADP/ATP carrier (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yeast ADP/ATP carriers have one brace and three salt bridges in the extended matrix network, providing a significant energy barrier that prevents conversion to the m-state in the absence of substrate. A single substrate-binding site has been identified in the central cavity, which corresponds to the middle of the membrane (25,29). There is consensus on the residues involved in ADP binding to the ADP/ATP carrier (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous proposals for the mechanism were based on a functional dimer (19,21,22), but subsequent work has shown that carriers are functionally monomeric (23,24). The first step toward a mechanism consistent with a monomeric carrier was the identification of a single substrate-binding site in the central cavity, as shown by distance and chemical constraints (25), molecular dynamics simulations (26,27), sequence analysis (28), and mutagenesis (29). Sequence analysis of the three homologous repeats found in members of the mitochondrial carrier family highlighted a conserved motif [YF][DE]xx[KR] on the cytoplasmic side, which has been suggested to form a salt-bridge network when the carrier is in the m-state (28).…”
mentioning
confidence: 99%
“…The coding sequences for SLC25A2 (NM_031947), SLC-25A12 (NM_003705), SLC25A13 (NM_014251), SLC-25A15 (NM_014252), SLC25A18 (NM_031481), SLC-25A22 (NM_024698), and SLC25A29 (NM_001039355) were amplified as perviously described (Fiermonte et al 2002(Fiermonte et al , 2003Lasorsa et al 2003;Monné et al 2012;Porcelli et al 2014). The amplified products were cloned into the pRUN (SLC25A2, SLC25A15, SLC25A18, SLC25A22, and SLC25A29), the pMW7 (SLC25A12), and pET-15b (SLC25A13) expression vectors and transformed into E. coli DH5α cells.…”
Section: Construction Of Expression Plasmidsmentioning
confidence: 99%
“…Molecular modeling of residue p. Arg179 showed from the lateral side (d) or from the top (e), with the side chain exposed to the inner part of the pocket. AAC1 protein was used as template (Monne et al 2012). The presence of a glutamine in position 179 impairs the ability of ORNT2 to complement DArg11 yeast cells, suggesting that ORNT2 functions primarily as a transporter of compounds other than ornithine.…”
Section: Discussionmentioning
confidence: 99%